LEGAL PROTECTION OF DEBUS ARTS IN THE ADVANCEMENT OF LOCAL UNIQUENESS-BASED CULTURE - Purwaningsih, endang; Islami, Irfan; Basrowi; Agil, Achmad Said (Universitas Serang Raya, 2024)
This research aims to (1) analyze the form of legal protection of Debus art both in cultural advancement regulation and in copyright; and (2) propose a Model that is appropriate in enhancing the role of related stakeholders in Banten Province for the implementation of Debus protection. This research falls under normative juridical research emphasizing secondary data supported by interviews with informants as supporters, examining positive law (IPR/Copyright and Cultural Advancement). The output of this research is targeted for a scientific publication in the form of a model to increase the role of stakeholders for the protection of Debus Banten. The research results show that 1. The form of legal protection of Debus art needs to be enhanced not only through preservation carried out by Debus performers and their associations, but also stakeholder synergy in regulation, promotion, and education. There are 4 pillars namely protection, development, guidance, and utilization, which are continuously strived for optimally. 2. The appropriate model in enhancing the role of related stakeholders in Banten Province for the implementation of Debus protection, with the optimization of the role of local governments in implementing 4 pillars, plus partnership patterns and partisanship